New Lead Schiff Bases Predominantly Mediate Vasorelaxant Activity Through α1 Receptor Blocking Activity - Zakia Subhan; Niaz Ali; Abid Ullah; Wajid Ali; Muhammad Nabi; Syed Wadood Ali Shah (Biomolecules)
Schiff bases synthesized in our laboratory have demonstrated pain-relieving effects through both peripheral and central nervous system pathways. Considering that centrally acting analgesics often affect the muscle tone of the gastrointestinal tract (GIT) and related deep internal organs, this study was conducted to examine potential relaxant effects on blood vessels and GIT smooth muscles. The possible relaxant effects of Schiff bases (SB1 and SB2) on isolated rabbit aortic strips were evaluated. The experiments involved assessing their impact on contractions induced by 80 mM potassium chloride (KCL) and 1 µM norepinephrine (NE). Norepinephrine concentration response curves (N. ECRCs) were constructed in the absence and presence of three different concentrations of SB1 and SB2, using N. ECRCs as a negative control. Terazosin served as a standard α1 receptor blocker. Docking studies were employed to validate the mechanism of action for SB1 and SB2. The study outcomes suggest that SB1 is more potent than SB2, demonstrating lower EC50 values for NE-induced contractions in intact (5.50 × 10−5 ± 2.23 M) and denuded (5.81 × 10−5 ± 3.80 M) aortae. For NE-induced contractions, SB1 showed percent relaxation values of 48% and 41% in intact and denuded aortae, respectively. In comparison, SB2 exhibited values of 82.5% and 74%, showing that SB1 is more efficacious than SB2. The rightward shift of N. ECRCs for both SB1 and SB2 confirms their inhibition of α1 receptors. Additive effects of SB1 and SB2 were seen in the presence of verapamil (p < 0.0001). Docking analysis revealed that the compounds can properly bind to the target receptor Gq 1D (P25100). Findings show that both Schiff base SB1 and SB2 produce significant (p < 0.05) vasorelaxation via the α1 receptor blocking mechanism.